To Investigate the Potential Mechanisms By Which A Combination of Zinc, Fructose, And Pumpkin Seeds Affects Infertility-Related Diseases - Goswami, Anjali; Singh, Sonalika (Journal of Neonatal Surgery, 2025)
Infertility, particularly male infertility, is a growing global concern with declining sperm quality being a major contributing factor. The present study evaluated the effects of combined supplementation of zinc, fructose, and pumpkin seeds on reproductive function and systemic health in male Wistar rats. Twenty-four rats were divided into four groups: control, 100 mg/kg, 150 mg/kg, and 200 mg/kg, administered orally for eight weeks. Hematological, biochemical, hormonal, and semen parameters were assessed alongside histopathological examinations of vital organs. Results showed that 100 mg/kg supplementation improved reproductive health with enhanced germ cell development and stable systemic function. The 150 mg/kg group exhibited the most beneficial effects, including optimal hematological and biochemical stability, normal liver and kidney function, high-normal testosterone levels (7.2–7.6 ng/mL), and significantly improved semen parameters (sperm count 100–118 million/mL, motility 76–84%, progressive motility 54–68%, viability 86–92%, morphology 74–85%, semen volume 2.0 mL). Histological findings confirmed well-preserved tissue integrity across multiple organs with vigorous spermatogenesis. Conversely, the 200 mg/kg group demonstrated peak semen parameters (sperm count 120–122 million/mL, motility 88–92%), but severe systemic toxicity including renal tubular necrosis, testicular degeneration, pancreatic and cardiac damage, and fibrosis in reproductive tissues. Overall, supplementation with zinc, fructose, and pumpkin seeds at moderate levels (100–150 mg/kg) enhanced male fertility, with 150 mg/kg identified as the most effective and safest dose, whereas supraphysiologic dosing (200 mg/kg) caused significant organ toxicity.